Case report: A rare case of meningoencephalitis caused by Mycobacterium gordonae - Yuan, Dezhi; Ding, Xiaomi; Chen, Jing; Zhao, Ying; Wang, Xing; Zhu, Jie (Frontiers in Medicine, 2024)
Meningoencephalitis, an infectious disease affecting the nervous system, is primarily caused by a variety of pathogens. Non-tuberculous mycobacteria (NTM) have emerged as the leading causative agent of infections worldwide, but central nervous system infections resulting from NTM are infrequent in individuals with functioning immune systems. This case report highlights the diagnosis and treatment of a 26-year-old female patient who developed headaches 2 months post double eyelid surgery and was subsequently diagnosed with NTM meningoencephalitis through metagenomic next-generation sequencing (mNGS) analysis of cerebrospinal fluid. The patient underwent a comprehensive diagnostic and therapeutic protocol, resulting in a positive clinical outcome.